GEL NANOEMULSION OF RAMBUTAN (NEPHELIUM LAPPACEUM L.) FRUIT PEEL EXTRACTS: FORMULATION, PHYSICAL PROPERTIES, SUNSCREEN PROTECTING, AND ANTIOXIDANT ACTIVITY - Muhtadi; Suhendi, Andi; Wikantyasning, Erindyah Retno (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The aim of this study is to determine the optimum formulation of gel nanoemulsion of the rambutan fruit peel extracts (RFPEs), sunscreen protecting factor, and antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric thiocyanate (FTC) methods. Materials and Methods: Formulation was optimized based on the variety of concentrations of RFPE, namely, 0.25%; 0.38%; 0.51%; and 0.63%. Gel nanoemulsion was characterized based on a number of the physical and chemical properties, such as pH, viscosity, adhesion, spread property, stability, and particle size. Sunscreen protecting factor and antioxidant activity were conducted using spectrophotometer ultraviolet-visible. Results: The result showed that the particle size of gel nanoemulsion formulation 1 (FI), FII, FIII, and FIV were at 13.30Â±4.00 nm, 1.90Â±9.70 nm, 2.70Â±13.60 nm, and 14.50Â±2.50 nm, respectively. Based on transmission electron microscopy image, it showed that formula with the concentration of 0.25% of RFPE could form nanoemulsion particle aggregate with good dispersion. The varied concentrations of RFPE statistically indicated no significant differences among adhesive, spread property, and viscosity of all formulas. Formula 1 showed the highest sunscreen protecting factor with the value of sun-protecting factor at 6.450Â±0.002, followed by F4, F3, and F2 with the values in sequence at 9.370Â±0.002, 10.120Â±0.001, and 13.120Â±0.001, respectively. The antiradical activity of the gel nanoemulsion RFPE with inhibitory concentration 50% (IC50) value was at 9.32Â±0.05 Î¼g/ mL. Meanwhile, the higher value of branded product and Vitamin E, which IC50 were 40.41Â±0.97 and 10.41Â±0.05 Î¼g/mL, respectively. In contrast, gel nanoemulsion of RFPE had the lowest inhibition on FTC method. The highest inhibition potency was showed by Vitamin E (79.07Â±7.62%), followed by branded product (60.07Â±13.23%) as comparison. Conclusions: The gel nanoemulsion of RFPEs of FIII had a good physical stability and sunscreen protection activity. The antioxidant activity of gel nanoemulsion of RFPE by DPPH and FTC methods were IC50 value of 9.32Â±0.05 Î¼g/mL and % inhibition of 51.09Â±0.99%. Â